PENGARUH PRENATAL GENTLE YOGA TERHADAP LAMA PERSALINAN KALA I FASE AKTIF PADA IBU PRIMIGRAVIDA DI PMB W.M - Suhartati, Susanti; Lisda Handayani; Winda Maolinda (LPPM Universitas Sari Mulia, 2023)
Background: Prenatal gentle yoga is believed to help reduce the duration of active phase I labor in primigravida mothers, which is often a risk factor for complications such as bleeding, fatigue, and medical interventions such as cesarean section. The duration of labor not only increases the risk of complications for the mother, but also affects the baby's condition. Therefore, non-invasive interventions are needed that can speed up the natural labor process. Prenatal gentle yoga was introduced as a method that helps facilitate labor through breathing techniques, postures, and relaxation that are suitable for pregnant women. Methods:This study used a quasi-experimental design with two groups, namely the intervention group who attended prenatal gentle yoga classes and the control group who did not. A total of 30 primigravida pregnant women participated, consisting of 15 people in the intervention group and 15 in the control group. The duration of active phase I labor was observed and analyzed using statistical tests to see significant differences between the two groups. Result: The results showed that the group that participated in prenatal gentle yoga had an average labor duration of 5 hours, while the control group had 7 hours. Statistical analysis with the Mann-Whitney test resulted in a p-value <0.05, indicating a significant effect of prenatal gentle yoga on accelerating labor. Conclusion: Prenatal gentle yoga is an effective intervention to accelerate active phase I labor in primigravida mothers, making a significant contribution to midwifery practice. Prenatal yoga can be used to reduce the risk of complications due to prolonged labor and improve the quality of maternal and infant health care, and accelerate postpartum recovery. Keywords:: Prenatal gentle yoga, labor, stage I, active phase, primigravida mothers.